Impact of New Technologies and Approaches for Post–Myocardial Infarction Ventricular Tachycardia Ablation During Long-Term Follow-Up. (July 2016) - Yamashita, Seigo; Cochet, Hubert; Sacher, Frédéric; Mahida, Saagar; Berte, Benjamin; Hooks, Darren; Sellal, Jean-Marc; Al Jefairi, Nora; Frontera, Antonio; Komatsu, Yuki; Lim, Han S.; Amraoui, Sana; et al.
Abstract : Background—: During the past years, many innovations have been introduced to facilitate catheter ablation of post–myocardial infarction ventricular tachycardia. However, the predictors of outcome after ablation were not thoroughly studied. Methods and Results—: From 2009 to 2013, consecutive patients referred for post–myocardial infarction ventricular tachycardia ablation were included. The end point of the procedure was complete elimination of local abnormal ventricular activities (LAVA) and ventricular tachycardia (VT) noninducibility. The predictors of outcome with primary end point of VT recurrence were assessed. A total of 125 patients were included (age: 64±11 years; 7 women) for 142 procedures. The left ventricle was accessed via transseptal, retrograde aortic, and epicardial approaches in 87%, 33%, and 37% of patients, respectively. Three-dimensional electroanatomical mapping system was used in 70%, multipolar catheter in 51%, and real-time image integration in 38% (from magnetic resonance imaging in 39% and multidetector computed tomography in 93%) of patients. Before ablation, VT was inducible in 75%, and endocardial/epicardial LAVA were present in 88%/75%. After ablation, complete LAVA elimination was achieved in 60%, and VT noninducibility in 83%. During a median follow-up of 850 days (interquartile range, 439–1707), VT recurrence was observed in 36%. Multivariable analysis identified 3 independent outcome predictors: the ability to achieve complete LAVA elimination ( R 2 =0.29; P <0.0001; risk ratio=0.52 [0.38–0.70]), the use of real-time image integration ( R 2 =0.21; P =0.0006; risk ratio=0.49 [0.33–0.74]), and the use of multipolar catheters ( R 2 =0.08; P =0.05; risk ratio=0.75 [0.56–1.00]). Conclusions—: Achievement of complete LAVA elimination and use of scar integration from imaging and multipolar catheters to focus high-density mapping are independent predictors of VT-free survival after catheter ablation for post–myocardial infarction ventricular tachycardia.